PEMBUATAN PETA SITUASI DUSUN BANARAN & TRUKAN DESA BAYURIPAN KECAMATAN BAYAT KABUPATEN KLATEN PROPINSI JAWA TENGAH - , AMBAR WASKITO S ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The final task is explains about collecting procedures and processing of the measured data to produce maps of spatial data information. Spatial data include the coordinates X, Y, Z are presented in map form. Activity-making framework that is used is in the form of map control measurement and control framework horizontal vertical control framework, the measurement of planimetric detail and a high point, as well as digital imaging. The end result is a situation map scale of 1: 500 Hamlet Banaran and Trukan, Banyuripan Village, Bayat sub district, Klaten district, Central Java province. In the system of UTM (Universal Transverse Mercator).